The Region of the Upper Msta River in the early middle ages - Islanova, Inna Vasilʹevna, 1953- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2021)
This is a book about the archaeological sites of the 5th to 8th century of the Volga-Baltic watershed in the forest zone of Eastern Europe. The region has long been known for burial assemblages of the so-called culture of the Pskov long barrows, but the book brings to light a different group of sites. The population living on those sites co-existed with those who buried their dead under the Pskov long barrows, but within a different landscape. This polarity suggests that the local population was behind the culture of Pskov long barrows, while the new category of site point to immigrants from the southwest. The book suggests that the "new" archaeological sites were inhabited by a Slavic-speaking population from the periphery of the Kiev and Kolochin cultures.